2021
DOI: 10.1002/chem.202005085
|View full text |Cite
|
Sign up to set email alerts
|

In Situ X‐ray Diffraction Investigation of the Crystallisation of Perfluorinated CeIV‐Based Metal–Organic Frameworks with UiO‐66 and MIL‐140 Architectures**

Abstract: We report on the results of an in situ synchrotron powder X‐ray diffraction study of the crystallisation in aqueous medium of two recently discovered perfluorinated CeIV‐based metal–organic frameworks (MOFs), analogues of the already well investigated ZrIV‐based UiO‐66 and MIL‐140A, namely, F4_UiO‐66(Ce) and F4_MIL‐140A(Ce). The two MOFs were originally obtained in pure form in similar conditions, using ammonium cerium nitrate and tetrafluoroterephthalic acid as reagents, and small variations of the reaction p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
36
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 49 publications
3
36
0
Order By: Relevance
“…Furthermore, among these occurred Ce IV ‐MOFs, most of them have UiO‐66‐type architecture and thus their IBUs are dominated by the hexanuclear Ce−O clusters [7,8] . Very recently, several Ce IV ‐MOFs with MIL‐140 topology have been reported, in these frameworks the three‐dimensional (3D) network are constructed through the interconnection of the ligand molecules and the 1D IBU chains consisting of alternating edge sharing CeO 7 polyhedra [11,12] . To the best of our knowledge, this is the first IBU that is not based on the hexanuclear Ce−O cluster in Ce IV ‐MOFs.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, among these occurred Ce IV ‐MOFs, most of them have UiO‐66‐type architecture and thus their IBUs are dominated by the hexanuclear Ce−O clusters [7,8] . Very recently, several Ce IV ‐MOFs with MIL‐140 topology have been reported, in these frameworks the three‐dimensional (3D) network are constructed through the interconnection of the ligand molecules and the 1D IBU chains consisting of alternating edge sharing CeO 7 polyhedra [11,12] . To the best of our knowledge, this is the first IBU that is not based on the hexanuclear Ce−O cluster in Ce IV ‐MOFs.…”
Section: Introductionmentioning
confidence: 95%
“…[7,8] Very recently, several Ce IV -MOFs with MIL-140 topology have been reported, in these frameworks the three-dimensional (3D) network are constructed through the interconnection of the ligand molecules and the 1D IBU chains consisting of alternating edge sharing CeO 7 polyhedra. [11,12] To the best of our knowledge, this is the first IBU that is not based on the hexanuclear CeÀ O cluster in Ce IV -MOFs. Therefore, new synthetic routes to Ce IV -MOFs, particularly these with novel IBUs, are highly desirable for the development and the multifunctional applications of Ce IV -MOFs.…”
Section: Introductionmentioning
confidence: 95%
“…20,22−24 We have recently reported on the water-based synthesis of two perfluorinated Ce IV analogues of the wellknown UiO-66 and MIL-140A framework types. 21,25 The ultramicroporous F4-MIL-140A(Ce) displays an S-shaped isotherm and outstanding CO 2 /N 2 selectivity, and it was also found to display inverse CO 2 /C 2 H 2 selectivity. 26 As a result of our continued effort in developing highly stable (per)fluorinated MOFs based on tetravalent metals for CCS applications, 27 we report herein on the preparation and solid-state characterization of a perfluorinated analogue of the well-known MOF-801, namely, Zr IV tetrafluorosuccinate (ZrTFS), and of the two mixed-linker perfluorinated MOFs (PF-MOFs) PF-MOF1 and PF-MOF2 through postsynthetic tetrafluorosuccinate/fumarate (Scheme 1) linker exchange starting from pure zirconium fumarate MOF-801.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Typical CO 2 adsorption sites in MOFs include coordinatively unsaturated metal ions and functional groups with a basic character on the organic linker. ,, A promising approach that is gaining momentum is to introduce fluorine atoms in the backbone of ultramicroporous MOFs to prepare new materials labeled as perfluorinated MOFs (PF-MOFs). , Besides increasing the thermodynamic affinity for CO 2 (as evidenced by a high isosteric heat of adsorption, Q st ), the presence of (per)­fluorinated groups can also render the framework hydrophobic, thus preserving the CO 2 capture performance in humid conditions, which is crucial for real-life applications. The family of hybrid ultramicroporous materials containing fluorinated anions such as SiF 6 2– , NbOF 5 2– , and TiF 6 2– represents an excellent example of how the presence of fluorine atoms exposed in narrow pores provides superior affinity for CO 2 while preserving a physisorption-based mechanism and minimizing competitive water adsorption. , We have recently reported on the water-based synthesis of two perfluorinated Ce IV analogues of the well-known UiO-66 and MIL-140A framework types. , The ultramicroporous F4-MIL-140A­(Ce) displays an S-shaped isotherm and outstanding CO 2 /N 2 selectivity, and it was also found to display inverse CO 2 /C 2 H 2 selectivity…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work showed that, due to the similarities between the powder X-ray diffraction (PXRD) patterns of the fcu and hcp MOFs, , it is not always immediately obvious that a MOF structure with a different cluster has formed. Despite advances in understanding, including studies on the effects of different variables (including acid modulator, water, and organic linker) on the crystallization of UiO-66 (zirconium , and cerium analogues), the focus of much current research is on the crystallization process rather than the metal cluster formation, which directs the crystallization. A full picture of the formation routes of MOFs is therefore still far off.…”
Section: Introductionmentioning
confidence: 99%